Strategic management of digital communication in the Ecuadorian company. Comparative perspective with the European reality - Cadme Samaniego, I. (2017)
In the era of digital convergence, organizations achieving a model that relates management interests and public symmetries require the construction of an image and reputation through strategic communication planning. However, this systemic approach-in which communication traverses all processes in the organization-is not a constant in Ecuadorian companies, as found an analysis of communications professionals in various companies. This article is the result of research conducted by the Observatory of Strategic Communication of Ecuador in the Universidad Tecnica Particular de Loja-Ecuador, formed in 2013 to study the professional profile of journalists in the field of internal, corporate, digital media and business as well as overall corporate social responsibility. The first year of the study has focused on identifying the current status of strategic communication in terms of professionals trained for this role, organization, functions of strategic communication in business, strategies and actions performed, and trends. The results reported in this paper have been compared with some of the results found in the European Communication Monitor 2014. Both in Europe and in Ecuador, the trend of using technologies for the various tasks and activities in the area of communication increases. It is then necessary to find a common platform for dialogue and contributions toward the same goal: to reach an approach that is balanced in a symmetric relationship with people.